Short Communication: Flora, life form and chorological study of Quercus brantii habitat in Emamzadeh Abdullah woodland, Iran - SINA ATTAR ROSHAN; MEHDI HEYDARI (Biodiversitas Journal of Biological Diversity, 2014)
Roshan SA, Heydari M. 2014. Flora, life form and chorological study of Quercus brantii habitat in Emamzadeh Abdullah woodland, Iran. Biodiversitas 15: 245-250. Flora in each region identified an important role in maintaining national reserves of each country toplay. Iran is one of the most important centers of plant diversity in to account old world comes closer to 22% of its 8000 plant speciesare exclusively. Emamzadeh Abdullah forest is located in southeastern Khouzestan province, Iran. The field data were obtained using 70 sample (20m x 20m) plots in a systematic random grid. The attributes include tree and shrub species type, number of each species and canopy coverage, which were recorded by measuring their small and large crown diameters in each sample plot. In order to record the herbaceous species, the Whitakerâ€™s snail plot method was applied, which resulted in 64 mÂ² of the minimum plot area. In this study, 154 plant species recognized from the area were identified and collected to 106 genera and 38 belong to the family. Families by Papilionaceae with 20 species, Poaceae with 20 species, Asteraceae with 19 species and Lamiaceae with 12 species and large plant families that total 46.1% of all species are included. Investigation of life forms species shows that Hemicryptophyte are the most important.